How Starbucks saved my life : a son of privilege learns to live like everyone else - Gill, Michael (Michael Gates) (New York : Gotham Books, 2008)
In his fifties, Michael Gates Gill had it all: a big house, a loving family, and a six-figure salary. By sixty, he had lost everything: downsized at work, divorced at home, and diagnosed with a slow-growing brain tumor, Gill had no money, no insurance, and no prospects. He took a job at Starbucks, and for the first time in his life, he was a minority--the only older white guy working with a team of young African-Americans. He was forced to acknowledge his prejudices and admit that his new job was hard. And his younger coworkers, despite half the education and twice the personal difficulties, were running circles around him. Crossing over the Starbucks bar was the beginning of a transformation that cracked his world wide open. When all of his defenses and the armor of entitlement had been stripped away, a humbler, happier and gentler man remained.--From publisher description.
Keywords: Gill, Michael; Starbucks Coffee Company -- Employees -- New York (State) -- New York -- Biography; Advertising executives -- New York (State) -- New York -- Biography; Marketing consultants -- New York (State) -- New York -- Biography; Coffeehouses -- New York (State) -- New York; Acoustic neuroma -- Patients -- Biography